Language as the tip of the iceberg? Shedding a critical light on 'hidden' discourse in digital platforms. (August 2021) - Moschini, Ilaria; Sindoni, Maria Grazia
Abstract: In digital scenarios, procedural instructions are instances of a kind of discourse that is pervasive yet little visible. These instructions define the information architectures of digital platforms themselves (van Dijck et al. 2019 ), construct the symmetries of relationships by determining hierarchies and dependencies among users and shape the context of digital communication. The pervasiveness of technical documentation, however, is inversely proportional to its accessibility, as this is generally hidden to the public behind the level of user interfaces. However, the impact that these instructions have on a wide range of discourse practices for end users (for example in terms of how apps are developed or how users' data are protected), make them worthy of investigation. By building on critical multimodal discourse analysis (van Leeuwen 2012, 2014; Machin 2013 ) and integrating discourse analysis with elements of information theory (Moschini 2018 ), we will analyze a set of Facebook technical documentation about the login authentication service, comparing how this service was presented to app developers before and after the Cambridge Analytica scandal (Cadwalladr and Graham-Harrison 2018 ). We will show that, far from being a neutral authentication service, Facebook Login indexes discourse practices that enact specific social roles. We will do so to shed a critical light on the multidimensional micro-circulation of power (Foucault 1980 ) by means of texts analysis of instructional tools, by triangulating heuristics from linguistics, multimodality and information theory.